2008
DOI: 10.2174/1874091x00802010016
|View full text |Cite
|
Sign up to set email alerts
|

2S Albumin Storage Proteins: What Makes them Food Allergens?

Abstract: 2S albumin storage proteins are becoming of increasing interest in nutritional and clinical studies as they have been reported as major food allergens in seeds of many mono- and di-cotyledonous plants. This review describes the main biochemical, structural and functional properties of these proteins thought to play a role in determining their potential allergenicity. 2S albumins are considered to sensitize directly via the gastrointestinal tract (GIT). The high stability of their intrinsic protein structure, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
210
4
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(232 citation statements)
references
References 134 publications
6
210
4
3
Order By: Relevance
“…Using human colon cancer cell line (Caco-2) monolayers, purified wheat allergen w5-gliadin and nsLTPs have been described to cross the barrier by the transepithelial route [66]. Moreover, the transepithelial uptake across Caco-2 cell has been described for 2S albumins [67], Ber e 1 (brazil nut) and Ses i 1 (sesame) [68]. The major respiratory soya bean allergen Gly m 1 (P34) was shown to be endocytosed by the intestinal EC line IPECJ-2 derived from neonatal piglet by the involvement of caveolae/lipid raft microdomains [69].…”
Section: Interaction Of Non-proteases With Ecmentioning
confidence: 99%
“…Using human colon cancer cell line (Caco-2) monolayers, purified wheat allergen w5-gliadin and nsLTPs have been described to cross the barrier by the transepithelial route [66]. Moreover, the transepithelial uptake across Caco-2 cell has been described for 2S albumins [67], Ber e 1 (brazil nut) and Ses i 1 (sesame) [68]. The major respiratory soya bean allergen Gly m 1 (P34) was shown to be endocytosed by the intestinal EC line IPECJ-2 derived from neonatal piglet by the involvement of caveolae/lipid raft microdomains [69].…”
Section: Interaction Of Non-proteases With Ecmentioning
confidence: 99%
“…However, the first one account for the majority of food-induced immune reactions. Generally, storage proteins contained in legume seeds, grains and nuts are the causative of allergy reactions upon ingestion, mainly due to the high stability under extremes of pH and temperature, and variable similarity in their primary sequence among these allergens [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…1, 2). Due to recent advances in molecular biology, several allergen molecules are now known to belong to the 2S albumin family [18], and IgE-binding epitope mapping studies have been conducted on several 2S albumin family allergens, including Ana o 3 [19], Ara h 2 [20], and Jug r 1 [21]. We previously reported that BWp16 contains a conserved motif of 8 cysteine residues, which is one of the characteristic features of members of the 2S albumin family, and that it exhibits homology with several 2S albumin family allergens, Ara h 6, Ric c 1, and Ara h 2 [12].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that BWp16 contains a conserved motif of 8 cysteine residues, which is one of the characteristic features of members of the 2S albumin family, and that it exhibits homology with several 2S albumin family allergens, Ara h 6, Ric c 1, and Ara h 2 [12]. Alignment of the 2S albumins suggested EGVRDLKE to be located in helix IV [12,18]. Unfortunately, the EGVRDLKE sequence in BWp16 had low sequence homology with the helix IV sequences in all other 2S albumin family allergens, as reported previously, even though linear IgE-binding epitopes of several 2S albumin proteins have been indicated to be located in helix IV.…”
Section: Discussionmentioning
confidence: 99%